Masculinity Expectations and Cyberbullying in Adolescent Digital Communication - Harys Kristanto; Elis Yulianti; Raihan Nur Ardiansyah; Liyan Putra (Information Technology and Science (ITScience), 2026)
This research explores the influence of digital masculinity pressure on cyberbullying behavior among males from Generation Z and Alpha in Indonesia. It does so by combining the concepts of hegemonic masculinity, social comparison, masculinity-related stress, and online disinhibition. Digital platforms are increasingly showcasing hyper-masculine ideals through algorithmic visibility, influencer culture, and competitive online engagements, which leads to increased psychological stress among young males. By applying a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS), information was gathered from 478 male participants on prominent platforms including TikTok, Instagram, WhatsApp, and online gaming spaces. The findings indicate that pressure related to digital masculinity greatly increases stress associated with masculinity, and that social comparison further amplifies this impact. Masculinity stress was identified as the most significant factor predicting cyberbullying. This suggests that boys who feel insufficient compared to digital standards of masculinity are more inclined to participate in mockery, exclusion, harassment, or aggressive humor as a way to compensate. The phenomenon of online disinhibition plays a notable role in cyberbullying, illustrating how a sense of anonymity and diminished responsibility encourage impulsive acts of aggression. The research finds that cyberbullying among Indonesian boys is influenced by psychological factors and motivated by the desire to gain attention in the digital environment. The results emphasize the importance of digital literacy, training for emotional resilience, and interventions at the platform level to reduce online aggression influenced by masculinity, as digital environments increasingly impact the development of adolescent identities.